P106: The HINTS exam: An often misused but potentially accurate diagnostic tool for central causes of dizziness. (May 2019) - Regis, A.; LePage, R.; Bodunde, O.; Turgeon, Z.; Ohle, R.
Abstract : Introduction : Dizziness is a common presentation in emergency departments (ED), accounting for 2-3% of all visits. The HINTS (Head impulse test, Nystagmus, Test of skew) exam has been proposed as a accurate test to help differentiate central from peripheral causes of vertigo. It is only applicable to patients presenting with acute vestibular syndrome (acute onset dizziness or vertigo, ataxia, nystagmus, nausea and/or vomiting, and head motion intolerance). We aimed to assess the diagnostic accuracy of HINTS in detecting central causes of dizziness and vertigo in adult patients presenting with AVS.Methods : We performed a medical records review of all patients with a presenting complaint of dizziness to a tertiary care ED between Sep 2014 and Mar 2018. We excluding those with symptoms >14days, recent trauma, GCS <15, hypotensive, or syncope/loss of consciousness. Data were extracted by 5 trained reviewers using a standardized data collection sheet. Individual patient data were linked with the Institute of Clinical Evaluation Science (ICES) database to assess for any patients with a missed central cause. The primary outcome measure was a central cause of dizziness; cardiovascular accident (CVA), transient ischemic attack (TIA), brain tumour (BT) or multiple sclerosis (MS) as diagnosed on either computed tomography, magnetic resonance imaging, neurology consult or diagnostic codes within ICES.Results : 3109 patients were identified and 2309 patients met the inclusion criteria, of those 450 patients (44% male) were assessed using HINTS exam. Of those examined with HINTS, 7 patients (1.6% - 4 CVA 2 TIA 1 MS) were determined to have a central cause for their dizziness. HINTS had a sensitivity of 28.6% (95%CI 3.7 – 71%), specificity 95% (95%CI 92.6-96.9%). Of the individuals assessed with HINTS, only 16 presented with AVS (3.6%), of which three patients were found to have a central cause (CVA 2, TIA 1). HINTS in AVS for all central causes is 66.7% (95%CI 9.4-99.2%)sensitive but is 100%(95%CI 15.8-100%) for CVA alone (excluding TIA). Only 38%(16/42) of patients presenting with AVS were assessed using the HINTS exam.Conclusion : The current use of HINTS is inaccurate and it is used inappropriately in a large number of patients. Future studies should focus on the correct implementation of HINTS in the ED only in patients presenting with AVS.